Зміст дефініції "якість вищої освіти" в контексті наукових поглядів представників східноєвропейських наукових шкіл - Мороз, Володимир Михайлович; Мороз, Світлана Анатоліївна (НТУ "ХПІ", 2017)
Розглянуто розвиток наукової думки щодо визначення категоріального змісту дефініції якості вищої освіти та визначено особливості його формулювання у межах сучасних наукових досліджень; за результатами аналізу змісту наукових поглядів представників східноєвропейських наукових шкіл щодо тлумачення дефініції "якість вищої освіти" було концептуалізовано її зміст; визначено чинники, які обумовлюють складність та багатогранність прояву змісту категорії якості вищої освіти, а також опрацьовано її авторське тлумачення.

The development of scientific thought as for determining the content of categorical definitions of quality of higher education was reviewed and the peculiarities of its formulation within the current scientific research were determined; based on results of the analysis of the content of scientific views of representatives of Eastern European research schools on the interpretation of the definition of "quality of higher education", its content was conceptualized; the factors that lead to complexity and diversity of manifestation of the category of quality of higher education were defined, as well as its author's interpretation was processed.
The content of the definition of "quality of higher education" in the context of scientific views of representatives of eastern European science schools
Keywords: професійна діяльність; професійна компетентність; система цінностей особистості; ВНЗ; professional competence; quality of educational purposes; system of personal values